Measurement of the Isotopic Composition of Molybdenum in Geological Samples by MC-ICP-MS using a Novel Chromatographic Extraction Technique - Li, J.; Liang, X.; Zhong, L.; Wang, Xuan-Ce; Ren, Z.; Sun, S.; Zhang, Z.; Xu, J. (Wiley-Blackwell Publishing, 2014)
A novel preconcentration method is presented for the determination of Mo isotope ratios by multi-collector inductively coupled plasma-mass spectrometry (MC-ICP-MS) in geological samples. The method is based on the separation of Mo by extraction chromatography using N-benzoyl-N-phenylhydroxylamine (BPHA) supported on a microporous acrylic ester polymeric resin (Amberlite CG-71). By optimising the procedure, Mo could be simply and effectively separated from virtually all matrix elements with a single pass through a small volume of BPHA resin (0.5 ml). This technique for separation and enrichment of Mo is characterised by high selectivity, column efficiency and recovery (~ 100%), and low total procedural blank (~ 0.18 ng). A 100Mo-97Mo double spike was mixed with samples before digestion and column separation, which enabled natural mass-dependent isotopic fractionation to be determined with a measurement reproducibility of < 0.09‰ (δ98/95Mo, 2s) by MC-ICP-MS. The mean δ98/95MoSRM 3134 (NIST SRM 3134 Mo reference material; Lot No. 891307) composition of the IAPSO seawater reference material measured in this study was 2.00 ± 0.03‰ (2s, n = 3), which is consistent with previously published values. The described procedure facilitated efficient and rapid Mo isotopic determination in various types of geological samples.